Problematics of Students' Discipline Value in Academic Activities and Non Academic - Wabiser, Yan Dirk; Irianto, Petrus (PT FORMOSA CENDEKIA GLOBAL, 2024)
Discipline is a state that is formed and trained through the values of obedience, adherence, loyalty, serenity, order, and order. This research aims to know the concepts of discipline and how to shape the values of student discipline in academic and non-academic activities on FKIP IPS Management at one of the universities in Papua. This research involved 36 students. The method used in this research is qualitative method with purposive sampling techniques. Research results show that the concepts of discipline in academic and non-academic activities are values and mental attitudes. The results of this research clarify and produce forms of disciplinary awareness of students of IPS FKIP in one of the universities in Papua, among others: a) time commitment; b) appreciation of time; c) feelings of shame, guilt and fear; d) agreement as a rule. Furthermore, the student discipline concept of IPS is part of the discipline of democracy and self-imposed discipline that arises from within because of the impulse of feelings, wills and own minds to obey or do by themselves with the emphasis of educational approach. Rules are guidelines and directions, accomplishments are rewards. If the student's attitude shows obedience and adherence, then it is awarded as an achievement.Discipline is a state that is formed and trained through the values of obedience, adherence, loyalty, serenity, order, and order. This research aims to know the concepts of discipline and how to shape the values of student discipline in academic and non-academic activities on FKIP IPS Management at one of the universities in Papua. This research involved 36 students. The method used in this research is qualitative method with purposive sampling techniques. Research results show that the concepts of discipline in academic and non-academic activities are values and mental attitudes. The results of this research clarify and produce forms of disciplinary awareness of students of IPS FKIP in one of the universities in Papua, among others: a) time commitment; b) appreciation of time; c) feelings of shame, guilt and fear; d) agreement as a rule. Furthermore, the student discipline concept of IPS is part of the discipline of democracy and self-imposed discipline that arises from within because of the impulse of feelings, wills and own minds to obey or do by themselves with the emphasis of educational approach. Rules are guidelines and directions, accomplishments are rewards. If the student's attitude shows obedience and adherence, then it is awarded as an achievement.